2017
DOI: 10.1016/j.apenergy.2016.12.095
|View full text |Cite
|
Sign up to set email alerts
|

Off-design performance of concentrated solar heat and coal double-source boiler power generation with thermocline energy storage

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Compared with wind power and photovoltaic, concentrated solar power (CSP) with thermal energy storage can generate stable un-interrupted electricity for different solar radiation condition, which seems to be a promising technology to replace coal as the main power generation technology. However, conventional standalone CSP plants face a lot of difficulties at present, such as the huge investment, lower efficiency compared to fossil fired plants and large scale of thermal energy storage (TES) system requirements, which hinder the large-scale utilisation of solar energy [4,5]. Integrating solar thermal energy into coal-fired power plant, also known as solar aided coal-fired power (SACP) system, has the potential to reduce the coal consumption in coal-fired power plant and overcome the above mentioned drawbacks of CSP Plants as well [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with wind power and photovoltaic, concentrated solar power (CSP) with thermal energy storage can generate stable un-interrupted electricity for different solar radiation condition, which seems to be a promising technology to replace coal as the main power generation technology. However, conventional standalone CSP plants face a lot of difficulties at present, such as the huge investment, lower efficiency compared to fossil fired plants and large scale of thermal energy storage (TES) system requirements, which hinder the large-scale utilisation of solar energy [4,5]. Integrating solar thermal energy into coal-fired power plant, also known as solar aided coal-fired power (SACP) system, has the potential to reduce the coal consumption in coal-fired power plant and overcome the above mentioned drawbacks of CSP Plants as well [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al considered a 200 MWe coal-fired unit as an example and investigated four different integration schemes, and the results show that the solar thermal to power efficiency can be over 36% for the solar heat at 260 ℃ [9]. Then, the thermal performance [6,[10][11][12][13], economic performance [14,15] and off-design performance [5,6,16] different modes of solar aided coal-fired power generation system through theoretical calculations [23]. These studies indicated that SACP system is a promising way for the large scale utilisation of solar energy with high efficiency and can reduce the fossil fuel load in the coal-fired power system.…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy utilisation systems (SEUS) have 37 different variations, such as photovoltaic (PV) solar cells and solar organic Rankine cycle 38 power generation systems. The design of SEUS is highly dependent on the law of solar 39radiation, such as the capacity of capacitance for the PV system, the thermal energy storage 40 size for the solar organic Rankine cycle power generation systems [1] or the solar field size for 41 the solar hybrid power plant [2] . However, solar radiation as a non-stable energy is affected by 42 multiple factors, including latitude, district, season and cloud distribution and so on [3] .…”
mentioning
confidence: 99%
“…radiation, such as the capacity of capacitance for the PV system, the thermal energy storage 40 size for the solar organic Rankine cycle power generation systems [1] or the solar field size for 41 the solar hybrid power plant [2] . However, solar radiation as a non-stable energy is affected by 42 multiple factors, including latitude, district, season and cloud distribution and so on [3] .…”
mentioning
confidence: 99%
See 1 more Smart Citation